Efficient Synthesis of Aminoquinolinium and Aminoquinazolinium Salt Series: Amination or N-Alkylation First? - Casanova, Marion C.; Fil, Maximilien; Zhao, Yuxi; Azas, Nadine; Redon, Sébastien; Vanelle, Patrice; Broggi, Julie (Synlett, 2023)
The pharmacokinetic properties and, in particular, the poor solubilities of lead drug compounds are often a major impediment to their future clinical development. One common and effective solution is generally to use salt forms. Efficient strategies for the synthesis of quinolinium and quinazolinium salt series with promising therapeutic activities are thus of major interest. This study compares different synthetic routes for the rapid preparation of monomeric and dimeric aminoquinolinium and aminoquinazolinium salts. The advantages and limitations of the different processes, especially the importance of step order, are discussed.
Keywords: aminoquinolinium salts; aminoquinazolinium salts; N,N′-bridging alkylation; amination; nucleophilic aromatic substitution